PENGARUH KREATIVITAS TERHADAP INTENSI BERWIRAUSAHA MELALUI EFIKASI DIRI SISWA SMKN 3 DEPOK - Anggita Asmarani; Widya Parimita; Christian Wiradendi Wolor (Lafadz Jaya Publisher, 2023)
This research aims to determine the influence of creativity on entrepreneurial intention through self efficacy of student’s class XII at SMKN 3 Depok. This research method uses quantitative research methods. The sampling technique used proportionate random sampling with a total sample of 155 students. Model in this research used a path analysis model using Structural Equation Modeling Partial Least Square (SEM-PLS) version SmartPLS 3.0. Based on the analysis, it was found that creativity had a significant direct effect on entrepreneurial intention, creativity had a significant direct effect on self efficacy, self efficacy had a significant direct effect on entrepreneurial intention, and creativity had a significat indirect effect on entrepreneurial intention through self efficacy.